2019
DOI: 10.1038/s41598-019-52505-x
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol S and Bisphenol A disrupt morphogenesis of MCF-12A human mammary epithelial cells

Abstract: Breast cancer is one of the most common cancers diagnosed in women worldwide. Genetic predisposition, such as breast cancer 1 (BRCA1) mutations, account for a minor percentage of the total breast cancer incidences. And thus, many life style factors have also been linked to the disease such as smoking, alcohol consumption and obesity. Emerging studies show that environmental pollutants may also play a role. Bisphenol-A (BPA) has been suspected to contribute to breast cancer development, and has been shown to af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
(48 reference statements)
2
12
0
Order By: Relevance
“…Interestingly, the accumulated DNA damage and epigenetic alterations, both of which represent an essential base for cellular transformation and cancer development, were accompanied by features of transformed phenotype such as increased cellular invasiveness consistent with some published reports [15,30,31,41,42]. Recent literature suggested that BPA can disrupt mammary epithelial cells organization into acinar structures [43], We also observed some increased cellular abilities to form colonies in soft agar (anchorage independent growth) in MCF7 while this effect was not noted in HME1 at the test conditions. Cellular transformation might take prolonged periods and/or increasing doses, or may be, exposure to combination of toxic agents or toxic agents and other condition such as obesity or chronic inflammation.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, the accumulated DNA damage and epigenetic alterations, both of which represent an essential base for cellular transformation and cancer development, were accompanied by features of transformed phenotype such as increased cellular invasiveness consistent with some published reports [15,30,31,41,42]. Recent literature suggested that BPA can disrupt mammary epithelial cells organization into acinar structures [43], We also observed some increased cellular abilities to form colonies in soft agar (anchorage independent growth) in MCF7 while this effect was not noted in HME1 at the test conditions. Cellular transformation might take prolonged periods and/or increasing doses, or may be, exposure to combination of toxic agents or toxic agents and other condition such as obesity or chronic inflammation.…”
Section: Discussionsupporting
confidence: 85%
“…This analog is commonly used in daily products, such as epoxy glues, thermal receipts, canned food stuffs, paper currencies, luggage tags, food cartons, and baby bottles [9,10,11]. Products in which BPS has been used as a component, such as thermal papers and plastics, are labelled as 'BPA-free' in marketing [12]. Environmental monitoring studies have reported the presence of BPS in indoor dust, foodstuff, sediments, surface waters, and sewage sludges in different countries [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In combination, BPA and BPS augment the capacity for non-tumorigenic breast cells to invade the lumen. These data suggest BPA and its BPS substitute affect mammary development and contribute to breast cancer development (61). Bisphenol S promotes the migration of TNBC cells in vitro through activation of YAP, a key effector of the Hippo pathway, by inhibiting its phosphorylation, which promotes YAP nuclear accumulation and up-regulation of its downstream genes such as CTGF and ANKRD1 (62).…”
Section: Bpa Analogsmentioning
confidence: 92%